1986
DOI: 10.1002/ar.1092160102
|View full text |Cite
|
Sign up to set email alerts
|

Ultracytochemistry of ouabain‐sensitive K+‐dependent p‐nitrophenyl phosphatase in rat incisor enamel organ

Abstract: Sprague-Dawley strain rats of 4-5 weeks old were perfusion-fixed with either a mixture containing 0.1 or 0.25% glutaraldehyde and 2% formaldehyde, or a 2% formaldehyde in 0.1 M sodium cacodylate buffer for 10 minutes. Non-decalcified 30-50-micron sections of the enamel organ taken from lower incisors were then processed for ultracytochemical demonstration of ouabain-sensitive, K+-dependent, p-nitrophenyl phosphatase, by use of the one-step lead method, representing the second dephosphorylative step of Na+-K+-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Conceivably, the low intracellular Na+ that this cotransport needs is accomplished by the activity of Na + , K + -ATPase in plasma membranes of the papillary layer (Garant and Sasaki 1986; Josephsen et al 2010; Wen et al 2014,) continuously pumping out 3Na + and importing 2 K + . In addition, other, yet unknown mechanisms must be operate in enamel organ cells to compensate for charge differences that result from increased negative charge when NBCe1 and Na + -K + exchangers are functional.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the low intracellular Na+ that this cotransport needs is accomplished by the activity of Na + , K + -ATPase in plasma membranes of the papillary layer (Garant and Sasaki 1986; Josephsen et al 2010; Wen et al 2014,) continuously pumping out 3Na + and importing 2 K + . In addition, other, yet unknown mechanisms must be operate in enamel organ cells to compensate for charge differences that result from increased negative charge when NBCe1 and Na + -K + exchangers are functional.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early proposal for a so-called "two-step" mineralization process in enamel formation (Weinmann et al, 1942;Marsland, 1952), the morphological and functional modulation of the ameloblasts through the secretion and maturation stages has received much attention (Kallenbach, 1968(Kallenbach, , 1980Reith, 1970;Hammarstrdm, 1971;Garant, 1972;Garant and Sasaki, 1986;Sasaki and Garant, 1986b). It has been suggested that shortened post-secretory maturation ameloblasts are specialized cells for active mineral transport (Kallenbach, 1968;Reith and Boyde, 1981 a;Takano et al, 1982a).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to enamel mineralization, our recent ultracytochemical studies of Ca-and Na-K-ATPases in the enamel organ cells indicated that neither rufflc-cnded nor smooth-endcd maturation ameloblasts possessed these enzymatic activities, which mediate active cellular transport of Ca across plasma membranes by an outwardly-directed Ca pump and a Na-Ca exchange system (Sasaki and Garant, 1986b;Garant and Sasaki, 1986). In addition, it has been well documented that the smooth-ended maturation ameloblast layer does form a passage route for substances of various molecular weights between the vascular region and the maturing enarmel surface Reith, 1981: Debari tclt., 1986;Josephsen, 1984;Kallenbach, 1980:, McKee et cil., 1986: Reith et ci.t 1984.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the Na + /K + ‐ATPase α 1, β 1, and β 3 subunits are expressed in enamel organ, most notably in the basolateral membranes, and/or in the basal portion of the cytoplasm in maturation‐stage ameloblasts. In an early study by Garant & Sasaki , where an enzyme‐based histochemical methodology was used to locate Na + /K + ‐ATPase pump activity in enamel organ cells, this pump activity was sensitive to ouabain and was most noticeable in the cells of the stratum intermedium and in papillary layer cells of both secretory‐stage and transition‐stage ameloblasts, with little expression evident in ameloblasts. However, since that study was published , it has been shown that rats have both ouabain‐sensitive ( α 2 and α 3) and ouabain‐resistant ( α 1) forms of Na + /K + ‐ATPase .…”
Section: Discussionmentioning
confidence: 99%
“…In an early study by Garant & Sasaki , where an enzyme‐based histochemical methodology was used to locate Na + /K + ‐ATPase pump activity in enamel organ cells, this pump activity was sensitive to ouabain and was most noticeable in the cells of the stratum intermedium and in papillary layer cells of both secretory‐stage and transition‐stage ameloblasts, with little expression evident in ameloblasts. However, since that study was published , it has been shown that rats have both ouabain‐sensitive ( α 2 and α 3) and ouabain‐resistant ( α 1) forms of Na + /K + ‐ATPase . Thus, the rat enamel‐organ Na + /K + ‐ATPase activity identified previously in this enzymatic‐based study may have excluded the ouabain‐resistant α 1 subunit profile, which is the focus of our report in rat ameloblasts using isotope‐specific antibody.…”
Section: Discussionmentioning
confidence: 99%